Evaluating the Attributes Affecting Customer Preferences for Fresh Pork Products: An Application of Kano Model and Conjoint Analysis - Mahatthanachosit, Nilamon; Chompu-inwai, Rungchat (Indonesia Academia Research Society, 2023)
The case study company manufactures and distributes a range of food products aimed at general consumers and restaurant and hotel businesses. The company needs to develop and improve its fresh pork products to meet the requirements of the customers who are restaurateurs in Chiang Mai province, Thailand, with the plan to increase market share, which is currently low in this segment. This study presents the use of the Kano Model combined with Conjoint Analysis (CA) to study the attributes that affect customer preferences for restaurateurs when making purchase decisions for fresh pork products. The research is in two principal phases. The first phase is an analysis using the Kano Model to determine fresh pork products' attributes and attribute levels. The six attributes obtained are then used further in the second phase, the CA to find the attributes affecting customer preferences in purchasing fresh pork products. In the CA part of this study, data were collected from a total of 100 restaurateurs in Chiang Mai. The results of this research found that the attributes most important to restaurateurs were freshness and cleanliness: very fresh and clean; followed by standards certification labeling: a government guarantee of quality; color of pork: pinkish red; amount of fat: 3%; price: 125 baht/kg and sliced: sliced by machine.